THE EFFECT OF SERVICE QUALITY ON PATIENT SATISFACTION AND ITS IMPACT ON PATIENT LOYALTY - Naurah, Gladdays; Paramarta, Vip; Purwanda, Eka (CV. Lafadz Jaya, 2024)
This study aims to analyze the effect of service quality on patient satisfaction and its impact on patient loyalty in hospitals. Good service quality is an important factor in building strong relationships with patients. Patients who are satisfied with the services they receive will tend to be more loyal and continue to use the same health services in the future. In addition, service quality can also affect how likely patients are to recommend the hospital to others. This study uses a quantitative method by distributing questionnaires to a number of patients in the hospital as respondents. The data were analyzed using a linear regression method to determine how much influence service quality has on patient satisfaction and loyalty. The results of the study showed that service quality has a significant effect on patient satisfaction, which ultimately strengthens their loyalty. Service quality is an intervening variable that strengthens the relationship between patient satisfaction and loyalty. Thus, to increase patient loyalty, hospitals must continue to improve their service quality.